Kemampuan Pemahaman Konsep Awal Siswa dalam Pembelajaran Fisika : Analisis Tingkat Pemahaman pada Materi Fluida Dinamis - Suherly, Tomy; Azizahwati, Azizahwati; Rahmad, M (Jurnal Paedagogy, 2023)
This study aims to analyze students’ initial conceptual understanding abilities in learning physics on dynamic fluid material. The method used descriptive quantitative research and as many as 100 students in class XI MAN 3 Pekanbaru City as the sample. The data collection technique was done by distributing questions via Google form to 100 students in classes XI MIA 2, XI MIA 3 and XI MIA 4. Data analysis on mastery of the material for each student was calculated based on comparing the scores obtained by students against the maximum score set. The results of this study indicated that students’ conceptual understanding of the problem indicators explaining and concluding belong to the medium category, and the problem indicators are classified as belonging to the high category. An average of > 33.33% was obtained, categorized as moderate. However, there were several indicators of questions where students’ understanding of concepts was categorized as low. It is concluded that students’ understanding of concepts is categorized as low. So, it is very necessary to have a learning design that can provide attractiveness and motivation for student learning so that students can understand the concepts of physics.